(untitled) (UCC Student Medical Journal, 2024)
Background: Dysphagia is a difficulty in swallowing. Cancer cachexia is a generalised muscle loss disorder common in patients with late-stage disease. The prevalence of dysphagia in patients with head and neck cancer is well documented. However, it is postulated that cancer cachexia can, through systemic muscle loss, cause weakening of swallowing muscles and dysphagia. This review aimed to evaluate the scope of the association between cancer cachexia (excluding head and neck cancer) and dysphagia. Methods: A systematic review was conducted using the PRISMA P guidelines. PubMed and Embase databases were searched for papers including terms related to (1) cancer, (2) cachexia and (3) dysphagia. Results were imported to Zotero software manager, where duplicates were removed. The remaining articles were screened using pre-determined eligibility criteria. Eligible papers were retained for data extraction, data synthesis and narrative synthesis. Risk of bias was evaluated using the CASP cohort and case control tools. Results: Four studies met the eligibility criteria. These papers reported an association between cancer cachexia and dysphagia, with odds ratios of 2.1 [P=0.033] and 1.8 [P=0.018]. Prevalence of dysphagia was 16% higher in cancer patients with cachexia. Conclusion: These findings suggest a positive association between cancer cachexia and dysphagia. However, due to the limited number of papers included, their heterogeneity and their limitations, it is difficult to draw a robust conclusion. Sarcopenia or neurodegenerative disease may have contributed to these results. Regardless, these four studies support the requirement for dysphagia assessment in patients with cancers outside swallow regions.